SENTUHAN RASA DI BALIK MAKNA LABA - Rosidi Rosidi; Austina Luckyta Mursy (Jurnal Akuntansi Multiparadigma, 2013)
Abtract: Sense of Touch in the Meaning of Profit. This study aims to reveal the meaning of profit according to the existing customs, traditions and cultures of Aisyiyah hospitals. This qualitative study employed ethnographic approach which is realist in nature, and was geared to find out the meaning of profit through customs and rituals that had been practiced in the hospital for a long time. The research found that profit in the hospital is, first, interpreted from the abstract dimension, that is in the form sense. Second, profit is a form of gratitude and happiness sense. Third, profit serves as a spreader of happiness.Abstrak: Sentuhan Rasa di Balik Makna Laba. Studi ini berusaha mengungkap makna laba sesuai dengan kebiasaan, tradisi dan kultur yang ada di Rumah Sakit Aisyiyah. Jenis penelitian ini adalah kualitatif dengan pendekatan etnografi realis, mencoba mengungkap makna laba melalui kebiasaan, adat istiadat, dan ritual yang telah berlangsung sejak lama di rumah sakit. Hasil penelitian ini adalah pertama, laba dimaknai dari bentuknya secara abstrak  yaitu rasa. Kedua, wujud laba sebagai rasa syukur dan rasa bahagia. Ketiga, laba berfungsi sebagai penebar rasa bahagia.